2006
DOI: 10.1128/aac.01316-05
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolution of β-Lactam-Resistant Haemophilus influenzae : 9-Year Surveillance of Penicillin-Binding Protein 3 Mutations in Isolates from Japan

Abstract: A total of 621 clinical isolates of Haemophilus influenzae collected in Japan between 1995 and 2003 were studied for their susceptibilities to several antimicrobial agents, ␤-lactamase production, and amino acid substitutions in penicillin-binding protein 3 (PBP 3). Over the four study periods (first period, 1995 to 1996; second period, 1997 to 1998; third period, 2000 to 2001; fourth period, 2002 to 2003), the susceptibilities to ␤-lactam agents decreased and the incidence of isolates with substitutions at po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
50
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 23 publications
4
50
0
Order By: Relevance
“…Furthermore, a prospective prevalence study in Japan in 1999 showed that 55.1% of the H. influenzae strains were BLNAS, 3% were BLPAR, 26.4% were intermediateresistant strains, and 13.2% were BLNAR (35). The increase in the percentage of BLNAR strains has led to serious problems in the treatment of infectious disease in Japan (26,(31)(32)(33). Unfortunately, there is still limited information about the precise prevalence and dissemination of antimicrobial-resistant pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a prospective prevalence study in Japan in 1999 showed that 55.1% of the H. influenzae strains were BLNAS, 3% were BLPAR, 26.4% were intermediateresistant strains, and 13.2% were BLNAR (35). The increase in the percentage of BLNAR strains has led to serious problems in the treatment of infectious disease in Japan (26,(31)(32)(33). Unfortunately, there is still limited information about the precise prevalence and dissemination of antimicrobial-resistant pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…MICs of the Etest were rounded up to the next log 2 concentration, and agreement was defined as the results of broth microdilution and those of Etest in the range of Ϯlog 2 1 of each other. The mutation status of the ftsI gene in all strains was checked by using primers described previously (3,8). MICs of BLNAS and beta-lactamase-positive ampicillinresistant (BLPAR) strains showed consistent results by both tests, and the agreement was 92.59 to 100% for beta-lactams and 90 to 92.59% for meropenem, respectively.…”
mentioning
confidence: 99%
“…Low BLNAR strains are infrequently isolated, and their rates are increasing all of the world. [18][19][20] Occasionally low BLNAR strains will be classified as resistant because recurrent MIC determinations can be expected to be different by a size of positive or negative a fold concentration. 21 In pediatric isolates nontypeable H. influenzae was the predominant seroytpe.…”
Section: Discussionmentioning
confidence: 99%